Representation of Muslim Woman's Identity in "Assalamualaikum Calon Imam" Movie - Khairul Syafuddin (2021)
Muslim women who were initially seen as women who focused on religion, in this film showed that Muslim women are also capable of being an academic and have other activities that tend to be done by men. This study aims to determine how the identity of modern Muslim women is shown through film media. This research uses Roland Barthes semiotic analysis method. This semiotic analysis focuses on reading texts through the stages of reading denotative meanings, connotative meanings, and then connecting with myths in analyzing the signs that are shown through scenes in the film. The results of this study indicate that Muslim women played by Fisya presented that women have the freedom to choose fashion and activity. Muslim women's fashion shown through the character Fisya is adjusted through the activities she does, thus showing that Muslim women's fashion can adjust to the situation. In addition, the activity also shows that Muslim women also have the freedom to determine what they want, starting in terms of academics and hobbies.